Textbook Analysis of “Grow with English” For Sixth Grade: Alignment with the Merdeka Curriculum - Komala, Oktia Tri; Syamsiah, Nur; Riyadi, Sugeng (Journal of English Language and Education, 2025)
Analysing the textbook is necessary to ensure its alignment with the goals that are promoted by the curriculum. This study aims to evaluate the alignment of the exercises in the Grow with English textbook for sixth-grade elementary school with the Merdeka Curriculum, focusing on Listening and Speaking elements in learning outcomes of Phase C (grades V and VI).  Employing a content analysis, the textbook was analysed based on a checklist rubric adapted from Akhmad et al. (2022). The research examines the textbook’s content relevance, language skills coverage, cultural appropriateness, visual design, grammar and vocabulary, and methodological approaches. Findings reveal the textbook partially fulfils the Merdeka Curriculum expectations but would benefit from enhanced intercultural integration, increased authenticity in tasks, and greater emphasis on project-based and autonomous learning to foster communicative competence and character development in learners. This research contributes to textbook evaluation and supports the improvement of English language instruction in primary education.